(untitled) (Journal of Parents and Teachers, 2025)
Writing dialogues is an effective tool to integrate science and literature in the classroom. Through research, argumentation, and creativity, students develop knowledge and communication skills, demonstrating that writing can connect disciplines and help understand and express the world in a fun and thoughtful way.